OBE Curriculum and EFL Learning: A Comparative Study between Khulna University and NUBTK - Shaikh, Hasan; Kabir, Md. Shahjahan (IJLHE: International Journal of Language, Humanities, and Education, 2025)
The alignment between OBE curricula and EFL learning outcomes plays a crucial role in shaping students’ language proficiency and academic success. This study aims at exploring the effectiveness of OBE in EFL context at KU and NUBTK through a comparative analysis of 80 undergraduate students’ perceptions. And their perceptions were collected through a survey questionnaire. The results suggest that KU students perceived clearer learning outcomes, better English proficiency, and a more structured integration of course materials. The effectiveness of feedback mechanisms, critical thinking enhancement, and real-world applications was also perceived to be higher at KU. In contrast, NUBTK students exhibited more varied responses, with a higher proportion of neutral perceptions, suggesting inconsistencies in curriculum implementation. Despite these differences, both institutions showed no statistically significant variation in reading and writing skill development, indicating comparable effectiveness in these areas. However, KU students perceived significantly stronger improvements in speaking confidence and analytical skills, reinforcing the notion that well-structured OBE implementation enhances student learning experiences. Nevertheless, to address the limitation of this study, future works should explore faculty perspectives, conduct longitudinal studies, and include qualitative methods. Moreover, institutions should refine their OBE frameworks to ensure that students acquire the linguistic and cognitive skills necessary for academic and professional success.